This is like having two equations.

One is

2x - 3 = 7

and the other is

-(2x - 3) = 7

Which is the same as

-2x + 3 = 7

So now we have to solve both equations.

2x - 3 = 7

2x = 10

x = 5

And

-2x + 3 = 7

-2x = 4

x = -2

**So, x = -2,5**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now